2015
DOI: 10.1007/s00374-015-1048-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification inhibitors mitigate earthworm-induced N2O emission—a mesocosm study

Abstract: In this study, the soils with or without earthworms (Eisenia fetida) were treated with one of the two following nitrification inhibitors (NIs): dicyandiamide (DCD) or 3,4-dimethylpyrazole phosphate (DMPP); then, the soils were incubated for 90 days in laboratory mesocosms. The cumulative nitrous oxide (N 2 O) emission increased from 74.08 μg N 2 O-N kg −1 in the control to 384.69 μg N 2 O-N kg −1 in the earthworm-treated soil. The addition of NI decreased the cumulative N 2 O emissions from soils by 67.1 % in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…1d). These could be further supported by a previous study that observed a similar effect of DMPP on soils amended with E. fetida (epigeic earthworm) (Wang et al 2015). However, the fluctuation ranges of 1 3 the earthworm-induced N 2 O emissions in our study were much greater than theirs.…”
Section: Dmpp Reduces N 2 O Emission Primarily By Suppressing Soil Ao...supporting
confidence: 89%
“…1d). These could be further supported by a previous study that observed a similar effect of DMPP on soils amended with E. fetida (epigeic earthworm) (Wang et al 2015). However, the fluctuation ranges of 1 3 the earthworm-induced N 2 O emissions in our study were much greater than theirs.…”
Section: Dmpp Reduces N 2 O Emission Primarily By Suppressing Soil Ao...supporting
confidence: 89%
“…With 0.42% nitrogen fertilizer as an active ingredient (3 mg kg −1 soil DMPP with 715 mg N kg −1 soil), DMPP was observed to slow oxidation considerably, and reduced N 2 O emissions by 83–95% under both 40% and 60% WFPS (water-filled porespace) [ 18 ]. The addition of 1% DMPP decreased the cumulative N 2 O emissions of soils by 73.4% [ 52 ]. DMPP with mineral fertilizers, and at a low concentration of 1%, specifically inhibited nitration and stabilized for several weeks [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the application of nitrification inhibitors reduced denitrification-produced N 2 O through decreasing the functional gene abundances of denitrifiers (Dong et al 2013a;Kou et al 2015;Wang et al 2015). Further research is highly desirable to relate the changes in microbial functional genes abundance to process rates.…”
Section: Effects Of Dmpp and Nbtpt On Denitrifiersmentioning
confidence: 99%